1984
DOI: 10.1136/jnnp.47.10.1125
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between delayed traumatic intracerebral haematoma and disseminated intravascular coagulation.

Abstract: SUMMARYThe relationship between delayed traumatic intracerebral haematoma and disseminated intravascular coagulation was investigated. Eighteen patients with delayed traumatic intracerebral haematoma were selected as the study subjects from 268 consecutive patients with head trauma and compared with another two groups of patients with closed head injury (20 cases) and with multiple injuries (24 cases). All cases had six laboratory studies for disseminated intravascular coagulation for 7 days. The results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Others, however, have not observed a correlation of these three factors with PHI. 7,35,42 Other studies indicate that progressive hemorrhage after head injury is associated with diffuse intravascular coagulation as defined by increased concentration of fibrin degradation products and low fibrinogen concentration. 15,20,43 These parameters may be more reliable markers of coagulopathy than PT, PTT, and platelet counts.…”
Section: Factors Associated With Phimentioning
confidence: 98%
“…Others, however, have not observed a correlation of these three factors with PHI. 7,35,42 Other studies indicate that progressive hemorrhage after head injury is associated with diffuse intravascular coagulation as defined by increased concentration of fibrin degradation products and low fibrinogen concentration. 15,20,43 These parameters may be more reliable markers of coagulopathy than PT, PTT, and platelet counts.…”
Section: Factors Associated With Phimentioning
confidence: 98%
“…[25][26][27][28][29][30] Fewer other studies reported no association between coagulopathy and bleeding progression in TBI. [31][32][33] This considerable variation is attributed to lack of consensus on TBI-coagulopathy definition, heterogeneity of patients involved, variable laboratory tests used in different studies and timing to perform these tests and CTs. [34][35] The presence of hypodense areas within the epidural hematoma on CT scan is thought to be related to coagulopathy, 36 yet its association with EDHP is lacking adequate investigations.…”
Section: Coagulopathy and Edhpmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Several studies have suggested that this DIC-like picture might play a role in the development of early and delayed intracranial hemorrhage in head injury. [3][4][5] Several studies have demonstrated that the occurrence of a DIC-like picture is a strong indicator of the severity of injury and poor prognosis.…”
Section: Cerebral Injury and Dicmentioning
confidence: 99%
“…Systemic abnormalities of coagulation seen following insults to the brain are a known entity. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In 2 conditions in particular, cranial trauma and subarachnoid hemorrhage, this phenomenon has been well documented and shown to have clinical significance. In cranial trauma, the occurrence of disseminated intravascular coagulation (DIC) has been shown to correlate with poor clinical outcome as well as expansion of hemorrhagic injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation